2021
DOI: 10.1590/0104-1428.04320
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on stacking sequence of Kevlar and natural fibres/epoxy polymer composites

Abstract: This paper investigates the stacking sequence of combined natural and synthetic fibres reinforced epoxy composites for better mechanical properties. The hybrid composites fabricated using vacuum assisted compression molding process with the natural and synthetic fibres layered in three different sequences such as type I, type II and type III where the synthetic fibers were placed alternatively. The ultimate tensile strength of composite type III was increased by 12% and 30% when compared to composite type I an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…For the experiments, rectangular specimens measuring 65 mm × 12.7 mm were cut from manufacture bi-layer composites. The experiment's target temperatures are 28 °C to 200 °C, with a heating rate of 4 °C per minute [36][37][38].…”
Section: Mechanical Testingmentioning
confidence: 99%
“…For the experiments, rectangular specimens measuring 65 mm × 12.7 mm were cut from manufacture bi-layer composites. The experiment's target temperatures are 28 °C to 200 °C, with a heating rate of 4 °C per minute [36][37][38].…”
Section: Mechanical Testingmentioning
confidence: 99%
“…Banu et al compared the effects of the stacking sequence of Kevlar and natural fibers/epoxy polymer composites by using aloe vera, bamboo, and palm fibers. They concluded that the aloe vera/palm-Kevlar hybrid composite gives the highest impact strength because aloe vera and palm fibres have better wettability with the matrix and synthetic fibers [ 105 ].…”
Section: Mechanical Properties Of Interply Hybrid Compositesmentioning
confidence: 99%
“…Alkaline treatment, by removing chemical constituents from a fiber, such as a hemicellulose, lignin, and pectin, increases the roughness topographies of the fiber surface. Physically, the presence of a rough surface provides a mechanical interlock between the fiber surface and the matrix, which can improve the interfacial bond between them [ 68 , 113 ]. In addition, the alkaline treatment modifies the cellulose structure, increasing its crystallinity and reducing impurities such as sugar, which acts as a setting retardant in mortars [ 67 ].…”
Section: Why Are Natural Fibers Treated For Application In Cementitio...mentioning
confidence: 99%